Vitamin D and inflammation - Zuljasri Albar (Indonesian Rheumatology Association, 2009)
The discovery that most body cells and tissues have vitamin D receptors and that some of them have the enzymatic machinery to convert the circulating form of vitamin D (25-hydroxyvitamin D) into the active form (1,25- dihydroxyvitamin D/1,25(OH)2D3 ) gave a new insight about the function of this vitamin. In the course of time, more and more evidences showed that a low vitamin D level leads to the occurrence or recurrenceof cardiovascular diseases, type II diabetes mellitus (DM), cell dedifferentiation (oncogenesis), and immune derangement (autoimmune diseases such as lupus, typeI DM, rheumatoid arthritis, and multiple sclerosis). Most researchers have agreed that a minimum 25(OH)D3 serum level of about 30 ng/ml or more is necessary for favorable calcium absorption and good health. Until proven otherwise, the balance of the research clearly indicates that oral supplementation in the range of 1,000 IU/day for infants, 2,000 IU/day for children, and 4,000 IU/day for adults is safe and reasonable to meetphysiologic requirements, to promote optimal health, and to reduce the risk of several serious diseases.